Gender, Work, and Nutrition: Policy Insights from LANSA. - Rao, Nitya. (Tufts University. Tisch Library., 2017)
This LANSA presentation highlights the gender wage and gender value gap in South Asian countries, and the impolications both those things have on nnutrition outcomes for mothers and children.